SMART IRRIGATION SYSTEM BERBASIS ARDUINO - candra, joni; Maulana, Algifanri (ELKHA : Jurnal Teknik Elektro, 2019)
Based on the Batam City government program to increase the food security of Batam City so as not to depend on other regions where Batam City has been fulfilling its basic needs such as rice, fruit and vegetables, import Â from West Sumatra and North Sumatra, the success of its food security program will specifically choose an island to develop agriculture because each island in the Batam Islands is not suitable to be designed as an industrial area so that the specificity of an island developed for agriculture is needed. To participate in supporting the Batam City government program in developing food security in agriculture, a good irrigation or irrigation system is needed. The problem of irrigation water distribution occurs when the amount of water available is smaller than the needs of irrigation water, especially during the dry season. So that efficient use of irrigation water is needed. The uneven distribution of water due to poor management of irrigation water sources will greatly affect the success of the production of an agricultural product. to build a smart irrigation system using soil moiture sensors and Arudino-based water level sensors, it can be seen that the prototype system can function because the components used work in the order, and the results are obtained when the sensor water level is greater than 600 then the LED lights live red and buzzer will sound loudly indicating water tank below the level, when the value of soil moisture sensor is greater or equal to 700 then the red LED light is on and the buzzer sounds low indicating dray soil conditions and the water pump / selenoid valve will be on and green LED lights will live, when the value of soil moisture sensor is smaller 700 then the live yellow LED lights show moist soil and water pump / selenoid valve conditions, and when the value of soil moisture sensor is smaller than 300 then the blue LED light will live shows Soggy soil and water pump / selenoid valve off, the prototype of the smart irrigation system has the same design as it has been made.